Role of Probiotics and Prebiotics in Human Health: A Review - , Vishnupriya Sethuraman, Hafeef Roshan K.T.; Shalini, M. Niharika, V. Sampath, J. R. Rajeshwar, Michelle C. Lallawmkimi (Archives of Current Research International, 2024)
Probiotics and prebiotics are essential components in maintaining and enhancing human health, primarily through their beneficial effects on gut microbiota. Probiotics, which are live microorganisms, and prebiotics, which are non-digestible food components, work synergistically to improve digestive health, enhance immune function, and support metabolic health. The historical evolution of probiotics and prebiotics has demonstrated their wide-ranging health benefits, from preventing gastrointestinal disorders such as irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD) to managing metabolic disorders like obesity and type 2 diabetes. Clinical applications highlight their role in reducing antibiotic-associated diarrhea, enhancing insulin sensitivity, and mitigating symptoms of allergies and autoimmune diseases. However, the field faces significant challenges, including the need for standardization and quality control, addressing individual variability in response, and ensuring safety and efficacy. The lack of uniform regulatory oversight further complicates the assurance of product reliability and effectiveness. Despite these challenges, emerging trends and innovations, such as next-generation probiotics and prebiotics, personalized nutrition based on microbiome profiles, and advances in biotechnology and bioinformatics, offer promising solutions. These advancements are poised to enhance the specificity and effectiveness of probiotic and prebiotic interventions. For example, genetically engineered probiotics and novel prebiotics derived from non-traditional sources are being explored for their unique health benefits. Personalized approaches can optimize dietary recommendations and supplement formulations based on individual gut microbiome compositions. Future research directions should focus on mechanistic studies to elucidate the specific pathways through which probiotics and prebiotics exert their effects, conducting robust and diverse clinical trials, and developing new strains and compounds from diverse sources. Regulatory frameworks need to be established to ensure the safety, efficacy, and quality of these products. By addressing these challenges and leveraging innovative approaches, probiotics and prebiotics can be optimized to provide personalized and effective health solutions, significantly impacting public health. Integrating these functional foods into daily dietary practices holds the potential for a new era of preventive and therapeutic nutrition, enhancing overall health and well-being.